Online Sobriety Communities for Women's Problematic Alcohol Use: A Mini Review of Existing Qualitative and Quantitative Research - Davey, Claire (Frontiers in Global Women's Health, 2021)
The increase in women's drinking is one of the most prominent trends in alcohol consumption in the UK in recent history, possibly exacerbated by COVID-19 lockdown measures. Higher rates of drinking are associated with substantial economic, health, and social costs. However, women are less likely to seek treatment for Alcohol Use Disorder (AUD) than men and have less successful treatment outcomes from traditional treatment paths, such as 12-step programs and in-patient care. Female heavy drinkers may also experience particular forms of gendered stigma that affect their experiences of addiction and recovery and their desire or ability to access these more “traditional” services. This review provides an overview of existing qualitative and quantitative research regarding online sobriety communities that are predominantly utilised by women, such as non-12-step alcohol online support groups (AOSGs) and temporary abstinence initiatives (TAIs). This is a small—but expanding—body of literature emerging as “sober curiosity” and “mindful drinking” are trending in Western contexts such as the UK, particularly amongst young women who do not identify with traditional, binary recovery language such as “alcoholic” and “addict.” This review highlights the gaps in research and concludes that further research regarding these new treatment pathways, and women's experiences when utilising them, must be conducted to provide more evidence-based options for women who want to address problematic drinking. Public health bodies could also learn more effective strategies from these innovative solutions to reduce alcohol consumption generally.